Making a profit from credit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Charles Nangwale explaining how the Malawi Rural Finance Company balances its goals, both supporting farmers and staying in business.